Sensing the squeeze: nuclear mechanotransduction in health and disease - Luv Kishore Srivastava; Allen J. Ehrlicher (Nucleus)
The nucleus not only is a repository for DNA but also a center of cellular and nuclear mechanotransduction. From nuclear deformation to the interplay between mechanosensing components and genetic control, the nucleus is poised at the nexus of mechanical forces and cellular function. Understanding the stresses acting on the nucleus, its mechanical properties, and their effects on gene expression is therefore crucial to appreciate its mechanosensitive function. In this review, we examine many elements of nuclear mechanotransduction, and discuss the repercussions on the health of cells and states of illness. By describing the processes that underlie nuclear mechanosensation and analyzing its effects on gene regulation, the review endeavors to open new avenues for studying nuclear mechanics in physiology and diseases.